Indonesian local governments' commitment to the quality of the education sector - YATUN, I.; MULYANI, S.; WINARNINGSIH, S.; SUKMADILAGA, C. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study aims to test empirically whether the commitment of regional heads and the oversight function of local parliaments influence the performance of education through the quality of education sector expenditure.  It is empirically proven that the commitment of regional heads and the oversight function of local parliaments have a significant and positive effect on improving the quality of government expenditure. Both variables also positively affect the performance of education in Indonesia indirectly through the quality of education sector expenditure. This study indicates that improving the quality of education sector expenditure improves educational performance. RESUMEN Este estudio tiene como objetivo probar empíricamente si el compromiso de los jefes regionales y la función de supervisión de los parlamentos locales influyen en el desempeño de la educación a través de la calidad del gasto del sector educativo. Se demuestra empíricamente que el compromiso de los jefes regionales y la función de supervisión de los parlamentos locales tienen un efecto significativo y positivo en la mejora de la calidad del gasto público. Ambas variables también afectan positivamente el desempeño de la educación en Indonesia indirectamente a través de la calidad del gasto del sector educativo. Este estudio indica que mejorar la calidad del gasto del sector educativo mejora su desempeño.